Cultivation of Chlorella sp. in a Closed System Using Mining Wastewater and Simulated Flue Gas: Biomass Production and CO2 Fixation Potential - Thiago J. T. Cruz; Guilherme Q. Calixto; Fabiana R. de A. Câmara; Dárlio I. A. Teixeira; Renata M. Braga; Sibele B. C. Pergher (Sustainable Chemistry, 2025)
Chlorella sp. was cultivated in a closed system using PET bottles (5 L) and with the continuous injection of air and commercial gas (98% CO2) and in simulated conditions (15% CO2, 73% N2, and 12% O2). The culture medium was prepared using well water and mining wastewater, the cultivation period occurred in a 10-day cycle, and the cell growth curves were evaluated through cell counting using a Neubauer chamber. The cultivation was carried out under the following conditions: temperature at 22 °C to 25 °C; aeration rate with commercial and simulated CO2 gas at 0.01 vvm; and synthetic air containing 0.042% CO2. The dry biomass productivity was 0.81 g·L−1·day−1 and the maximum CO2 fixation rate was 0.90 g·L−1·day−1 when the microalgae were cultivated with a continuous flow of simulated waste gas and a culture medium composed of wastewater. The percentages of macromolecules obtained in the biomass cultivated in wastewater reached 20.95%, 26.48%, and 9.3% for lipids, proteins, and carbohydrates, respectively.